1971
DOI: 10.1177/001316447103100304
|View full text |Cite
|
Sign up to set email alerts
|

Self-Claimed and Tested Knowledge

Abstract: EDUCATIONAL AND PSYCHOLOGICAL MEASUREMENT 1971, 31, 629-636. THE traditional method for observing whether or not a person knows something is to develop a test or examination which provides an opportunity for him to demonstrate his knowledge. The person is asked to indicate, through recall or recognition, the answer to a question and the person asking the question then decides regarding the correctness or appropriateness of the answer. The decision regarding the person's knowledge is a function of what he … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Self-reported data are widely used in research on college effects, and their reliability and validity have been extensively studied. (See Baird, 1976;Berdie, 1971;Pace, 1985 Pike, 1995;Pohlmann & Beggs, 1974.) These studies show that self-report measures are likely to be valid under five conditions: 1.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported data are widely used in research on college effects, and their reliability and validity have been extensively studied. (See Baird, 1976;Berdie, 1971;Pace, 1985 Pike, 1995;Pohlmann & Beggs, 1974.) These studies show that self-report measures are likely to be valid under five conditions: 1.…”
Section: Methodsmentioning
confidence: 99%
“…As listed in Table 1, these outcomes include the development of cognitive and socio-emotional capability, academic achievement, departure intention, and overall satisfaction. Studies have shown that at the aggregate level self reports provide reasonably stable estimates of such outcomes (Baird 1976;Berdie 1971;Laing et al 1989;Lowman and Williams 1987;Pike 1995;Pohlmann and Beggs 1974). While the capacity to engage in higher-order forms of thinking is a somewhat distinguishing characteristic of university education, it has not been directly measured in Australian higher education.…”
Section: Students' Engagement In Educationmentioning
confidence: 99%
“…A fair amount of research (Baird, 1976;Berdie, 1971;Pace, 1985;Pike, 1995;Pohlmann, 1974) has shown that self-reports are likely to be valid if (1) the information requested is known to the respondents, (2) the questions are phrased clearly and unambiguously, (3) the questions refer to recent activities, (4) the respondents think the questions merit a serious and thoughtful response, and (5) answering the questions does not threaten, embarrass, or violate the privacy of the respondent or encourage the respondent to respond in socially desirable ways ). The NSSE survey was designed to satisfy all of these conditions.…”
Section: Diversity At Liberal Arts Collegesmentioning
confidence: 99%